2020
DOI: 10.1186/s12974-020-1707-x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid beta and diabetic pathology cooperatively stimulate cytokine expression in an Alzheimer’s mouse model

Abstract: Background: Diabetes is a risk factor for developing Alzheimer's disease (AD); however, the mechanism by which diabetes can promote AD pathology remains unknown. Diabetes results in diverse molecular changes in the brain, including dysregulation of glucose metabolism and loss of cerebrovascular homeostasis. Although these changes have been associated with increased Aβ pathology and increased expression of glial activation markers in APPswe/ PS1dE9 (APP/PS1) mice, there has been limited characterization, to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 90 publications
1
32
0
Order By: Relevance
“…Some studies in older men have reported that men with the highest insulin levels, when performing the Mini-Mental State test, had 25% more errors compared to those with very low insulin levels [ 69 ]. The accumulation of amylin in the pancreas can decrease the level of insulin, which will lead to disruptions in carbohydrate metabolism (hyperglycemia) and will promote the development of neurodegenerative disorders [ 70 ]. The influence of high glucose levels on cognitive impairment was highlighted in the ACCORD-MIND study, which by assessing glycosylated hemoglobin (HbA1c) could detect the negative impact on cognitive tests [ 71 ].…”
Section: Amyloid Formation As a Common Pathological Feature In Botmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies in older men have reported that men with the highest insulin levels, when performing the Mini-Mental State test, had 25% more errors compared to those with very low insulin levels [ 69 ]. The accumulation of amylin in the pancreas can decrease the level of insulin, which will lead to disruptions in carbohydrate metabolism (hyperglycemia) and will promote the development of neurodegenerative disorders [ 70 ]. The influence of high glucose levels on cognitive impairment was highlighted in the ACCORD-MIND study, which by assessing glycosylated hemoglobin (HbA1c) could detect the negative impact on cognitive tests [ 71 ].…”
Section: Amyloid Formation As a Common Pathological Feature In Botmentioning
confidence: 99%
“…To more fully clarify neuro-inflammatory alterations related with diabetes that could drive AD pathology, Sankar and co-workers [ 70 ] quantified cortical modifications in cytokine proteins in three different models of mice, with metabolic changes relevant to diabetes combined with a mouse model of AD (APP/PS1). Multiplexed immunoassay showed that pathology associated with either pre-diabetes, db/db, or streptozotocin models led to the upregulation of a comprehensive profile of cytokines, comprising chemokines (macrophage inflammatory protein-1 alpha, MIP−1α; monocyte chemoattractant protein-1, MCP−1; and macrophage inflammatory protein-1 beta, MIP−1β) and proinflammatory cytokines (IL−1α; interferon gamma, IFN-γ; and IL−3).…”
Section: The Influence Of Amyloid-β Aggregates On Diabetes Patholomentioning
confidence: 99%
“…Following this idea, neuroinflammation also plays a significant role in neurodegeneration [ 10 ]. In this sense, AD brains suffer neuroinflammatory changes including alterations in morphology and distribution of microglia and astrocytes, or increased expression of inflammatory mediators [ 11 , 12 , 13 ]. While microglia’s response to injury is typically beneficial, it can go awry in cases of chronic injury and long-term inflammation, such as in AD.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Besides, TNF-α contributes to impair insulin signalling by increasing insulin receptor substrate-1 phosphorylation [ 61 ]. Altogether, it seems that T2DM, or even prediabetes, can cooperatively modulate the expression of brain pro-inflammatory cytokines in AD [ 12 ], and both the prediabetic state and T2DM, promote microglia activation in AD mice [ 62 , 63 , 64 ], supporting the role of the inflammatory process as a link between AD and T2DM.…”
Section: Ad-t2dm Relationshipmentioning
confidence: 99%
See 1 more Smart Citation